2022
DOI: 10.3389/fpls.2022.941338
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional deregulation of stress-growth balance in Nicotiana benthamiana biofactories producing insect sex pheromones

Abstract: Plant biofactories are a promising platform for sustainable production of high-value compounds, among which are insect sex pheromones, a green alternative to conventional insecticides in agriculture. Recently, we have constructed transgenic Nicotiana benthamiana plants (“Sexy Plants”, SxP) that successfully produce a blend of moth (Lepidoptera) sex pheromone compounds (Z)-11-hexadecen-1-ol and (Z)-11-hexadecenyl acetate. However, efficient biosynthesis of sex pheromones resulted in growth and developmental pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In previous studies we observed that constitutive expression impacts biomass (Juteršek et al, 2022;Mateos-Fernández et al, 2021). Although yields obtained using copper inducible promoters in transient infiltration were lower (12.4 µg Z11-16OH g -1 FW and 4.5 µg Z11-16OAc g -1 FW), than those that we obtained in previous studies using CaMV35s promoters (116.6 µg Z11-16OH g -1 FW and 110.1 µg Z11-16OAc g -1 FW), a lower yield per unit of biomass might be compensated for by high biomass production.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies we observed that constitutive expression impacts biomass (Juteršek et al, 2022;Mateos-Fernández et al, 2021). Although yields obtained using copper inducible promoters in transient infiltration were lower (12.4 µg Z11-16OH g -1 FW and 4.5 µg Z11-16OAc g -1 FW), than those that we obtained in previous studies using CaMV35s promoters (116.6 µg Z11-16OH g -1 FW and 110.1 µg Z11-16OAc g -1 FW), a lower yield per unit of biomass might be compensated for by high biomass production.…”
Section: Discussionmentioning
confidence: 92%
“…The economics of scaling-up production are likely to be different for different molecules, however, there is merit in comparing production methods. In previous experiments, we observed that the growth of transgenic lines of N. benthamiana producing the highest yields (per gram fresh weight) of the moth pheromones was negatively affected and photosynthesis-related genes were downregulated (Juteršek et al, 2022;Mateos-Fernández et al, 2021). Inducible gene expression systems are essential tools commonly employed to switch metabolism from growth to production, enabling biomass to accumulate before energy is redirected into the biosynthesis of desired products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although knowledge compiled in SKM is predominately based on Arabidopsis, this use case clearly shows its applicability in other species. Through orthology tools such as PLAZA (Van Bel et al ., 2022), the knowledge graphs in SKM can be translated to other species, as was done for the previous version of CKN to Prunus persica (Foix et al ., 2021), Solanum tuberosum (Ramšak et al ., 2018), and Nicotiana benthamiana (Juteršek et al ., 2022). This way, canonical principles of plant signalling networks can be assessed across species.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting transgenics accumulated Z11‐16OH, Z11‐16OAc, and Z11‐16Ald; however, plant growth was compromised in transgenic lines producing the highest yields. A subsequent analysis of transcriptional changes revealed stress‐like responses, including the downregulation of photosynthesis‐related genes (Juteršek et al ., 2022 ). Recent studies have also investigated the production of sex pheromone precursors in field‐grown transgenic Camelina sativa (false flax) (Wang et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%